Can subsyndromal manifestations of major depression be identified in children at risk?. (2nd November 2016) - Uchida, M.; Fitzgerald, M.; Lin, K.; Carrellas, N.; Woodworth, H.; Biederman, J.
Abstract : Objective: Children of parents with major depression are at significantly increased risk for developing major depression themselves; however, not all children at genetic risk will develop major depressive disorder (MDD). We investigated the utility of subsyndromal scores on the Child Behavior Checklist (CBCL) Anxiety/Depression scale in identifying children at the highest risk for pediatric MDD from among the pool of children of parents with MDD or bipolar disorder. Method: The sample was derived from two previously conducted longitudinal case–control family studies of psychiatrically and pediatrically referred youth and their families. For this study, probands were stratified based on the presence or absence of a parental mood disorder. Results: Subsyndromal scores on the CBCL Anxiety/Depression scale significantly separated the children at high risk for pediatric MDD from those at low risk in a variety of functional areas, including social and academic functioning. Additionally, children at genetic risk without elevated CBCL Anxiety/Depression scale scores were largely indistinguishable from controls. Conclusion: These results suggest that the CBCL Anxiety/Depression scale can help identify children at highest risk for pediatric MDD. If implemented clinically, this scale would cost‐effectively screen children and identify those most in need of early intervention resources to impede the progression of depression.